A review on adequacy of the Employment Act 1955 in protecting Indonesian maids in Malaysia / Wan Nurul Hidayah Wan Anuaruddin ... [et al.] - Wan Anuaruddin, Wan Nurul Hidayah; Jamaluddin, Mohamad Hafiz Firdaus; Mohd Daud, Muhammad Nur Firdaus; Muhammad Isa, Nur Annisa (2014)
This research looks into the Malaysian laws especially on Employment Act 1955 which govern the protections and rights of workers in Malaysia in particular on the issue of protection of Indonesian maid in Malaysia. Therefore, this research analyses the laws provided in order to protect the Indonesian maids' right in Malaysia in order to expose its incomprehensiveness in protecting them since most of Malaysian did employ them as their domestic helper. This research aims to find the possibility of reforming the laws of Malaysia concerning the protection of Indonesian maid. By using the doctrinal and empirical research method, this research looks into the possibilities of loopholes in Malaysian laws and guidelines used by our government in order to protect Indonesian maids that work in Malaysia and compare the steps taken between our government and others government to solve the cases of maid abuses faced by them. In the absence of comprehensive laws in protecting the rights for Indonesian maids working in Malaysia, this research is to fill in the gap. This research is also looking at the possibilities of amending the existing law for the protection of local or foreign maid for that matter.